The potential problem to explore students’ functional thinking in mathematical problem-solving - Tarida, Luthfiana; Budiarto, Mega Teguh; Lukito, Agung (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Many studies have reported that functional thinking plays a crucial role in mathematical problem-solving, particularly in fields requiring analytical reasoning, such as maritime studies. However, existing research has yet to comprehensively explore the specific task characteristics that effectively stimulate functional thinking in mathematical problem-solving, particularly among maritime students who must apply these skills in solving safety-of-life problems at sea. Addressing this gap, the present study investigates the potential of mathematical tasks in fostering functional thinking among second-semester students enrolled in the Deck Officer Program in Indonesia. The study involved three students with different mathematical abilities, who were given problem-solving tasks. Their responses were observed, recorded, and analyzed based on their written work. The findings reveal that non-routine problems involving functional situations—where students generalize relationships between varying quantities to determine function rules—effectively promote functional thinking. This is evidenced by the emergence of key functional thinking components, including problem identification, data representation, pattern recognition, covariational and correspondence relationships, and the evaluation of generalization rules. These results contribute to the development of research instruments in mathematics education and provide valuable insights for researchers and educators seeking to enhance functional thinking through task design.